Question
upstudy study bank question image url

\( \left. \begin{array} { l } { g ( x ) = - 5 x ^ { 2 } - 3 x + 4 } \\ { g ( 2 x ) = \square } \\ { 2 g ( x ) = \square } \\ { g ( x + 2 ) = \square } \\ { g ( x ) + 2 = \square } \\ { g ( x ) + g ( 2 ) = \square } \end{array} \right. \)

Ask by Hammond Huang. in the United States
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

g(2x) = –20x² – 6x + 4 2g(x) = –10x² – 6x + 8 g(x + 2) = –5x² – 23x – 22 g(x) + 2 = –5x² – 3x + 6 g(x) + g(2) = –5x² – 3x – 18

Solution

We are given the quadratic function   g(x) = –5x² – 3x + 4 and we want to find the following expressions:  1. g(2x)  2. 2g(x)  3. g(x + 2)  4. g(x) + 2  5. g(x) + g(2) Let's compute each one step by step. ────────────────────────────── 1. g(2x) Replace x with 2x in g(x):  g(2x) = –5(2x)² – 3(2x) + 4 First, compute (2x)² = 4x². Then:  g(2x) = –5(4x²) – 6x + 4       = –20x² – 6x + 4 ────────────────────────────── 2. 2g(x) Multiply g(x) by 2:  2g(x) = 2[–5x² – 3x + 4]      = –10x² – 6x + 8 ────────────────────────────── 3. g(x + 2) Replace x with (x + 2) in g(x):  g(x + 2) = –5(x + 2)² – 3(x + 2) + 4 First, expand (x + 2)²:  (x + 2)² = x² + 4x + 4 Now substitute in:  g(x + 2) = –5(x² + 4x + 4) – 3x – 6 + 4        = –5x² – 20x – 20 – 3x – 6 + 4 Combine like terms:  x² term: –5x²  x term: –20x – 3x = –23x  constant term: –20 – 6 + 4 = –22 Thus:  g(x + 2) = –5x² – 23x – 22 ────────────────────────────── 4. g(x) + 2 Simply add 2 to g(x):  g(x) + 2 = (–5x² – 3x + 4) + 2        = –5x² – 3x + 6 ────────────────────────────── 5. g(x) + g(2) First, compute g(2):  g(2) = –5(2)² – 3(2) + 4     = –5(4) – 6 + 4     = –20 – 6 + 4     = –22 Now add g(x) and g(2):  g(x) + g(2) = (–5x² – 3x + 4) + (–22)         = –5x² – 3x – 18 ────────────────────────────── Thus, the answers are:  • g(2x) = –20x² – 6x + 4  • 2g(x) = –10x² – 6x + 8  • g(x + 2) = –5x² – 23x – 22  • g(x) + 2 = –5x² – 3x + 6  • g(x) + g(2) = –5x² – 3x – 18

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To solve for the various forms of the function \( g(x) = -5x^2 - 3x + 4 \), let's break down each request: 1. For \( g(2x) \): \[ g(2x) = -5(2x)^2 - 3(2x) + 4 = -20x^2 - 6x + 4 \] 2. For \( 2g(x) \): \[ 2g(x) = 2(-5x^2 - 3x + 4) = -10x^2 - 6x + 8 \] 3. For \( g(x + 2) \): \[ g(x + 2) = -5(x + 2)^2 - 3(x + 2) + 4 = -5(x^2 + 4x + 4) - 3x - 6 + 4 = -5x^2 - 20x - 20 - 3x - 6 + 4 = -5x^2 - 23x - 22 \] 4. For \( g(x) + 2 \): \[ g(x) + 2 = (-5x^2 - 3x + 4) + 2 = -5x^2 - 3x + 6 \] 5. For \( g(x) + g(2) \): First, calculate \( g(2) \): \[ g(2) = -5(2)^2 - 3(2) + 4 = -20 - 6 + 4 = -22 \] Now, calculate \( g(x) + g(2) \): \[ g(x) + g(2) = (-5x^2 - 3x + 4) + (-22) = -5x^2 - 3x - 18 \] So plugging everything into the original blanks, we have: \[ \left. \begin{array} { l } { g ( 2 x ) = -20 x ^ { 2 } - 6 x + 4 } \\ { 2 g ( x ) = -10 x ^ { 2 } - 6 x + 8 } \\ { g ( x + 2 ) = -5 x ^ { 2 } - 23 x - 22 } \\ { g ( x ) + 2 = -5 x ^ { 2 } - 3 x + 6 } \\ { g ( x ) + g ( 2 ) = -5 x ^ { 2 } - 3 x - 18 } \end{array} \right. \]

Related Questions

ISCELÁNEA cribir, por simple inspección, el resultado de: \( \begin{array}{lll}(x+2)^{2} & \text { 14. }(x+y+1)(x-y-1) & \text { 27. }\left(2 a^{3}-5 b^{4}\right)^{2} \\ (x+2)(x+3) & \text { 15. }(1-a)(a+1) & \text { 28. }\left(a^{3}+12\right)\left(a^{3}-15\right) \\ (x+1)(x-1) & \text { 16. }(m-8)(m+12) & \text { 29. }\left(m^{2}-m+n\right)\left(n+m+m^{2}\right) \\ (x-1)^{2} & \text { 17. }\left(x^{2}-1\right)\left(x^{2}+3\right) & \text { 30. }\left(x^{4}+7\right)\left(x^{4}-11\right) \\ (n+3)(n+5) & \text { 18. }\left(x^{3}+6\right)\left(x^{3}-8\right) & \text { 31. }(11-a b)^{2} \\ (m-3)(m+3) & \text { 19. }\left(5 x^{3}+6 m^{4}\right)^{2} & \text { 32. }\left(x^{2} y^{3}-8\right)\left(x^{2} y^{3}+6\right) \\ (a+b-1)(a+b+1) & \text { 20. }\left(x^{4}-2\right)\left(x^{4}+5\right) & \text { 33. }(a+b)(a-b)\left(a^{2}-b^{2}\right) \\ (1+b)^{3} & \text { 21. }(1-a+b)(b-a-1) & \text { 34. }(x+1)(x-1)\left(x^{2}-2\right) \\ \left(a^{2}+4\right)\left(a^{2}-4\right) & \text { 22. }\left(a^{x}+b^{n}\right)\left(a^{x}-b^{n}\right) & \text { 35. }(a+3)\left(a^{2}+9\right)(a-3) \\ \left(3 a b-5 x^{2}\right)^{2} & \text { 23. }\left(x^{a+1}-8\right)\left(x^{a+1}+9\right) & \text { 36. }(x+5)(x-5)\left(x^{2}+1\right) \\ (a b+3)(3-a b) & \text { 24. }\left(a^{2} b^{2}+c^{2}\right)\left(a^{2} b^{2}-c^{2}\right) & \text { 37. }(a+1)(a-1)(a+2)(a-2) \\ (1-4 a x)^{2} & \text { 25. }(2 a+x)^{3} & \text { 36. }\left(x^{2}-11\right)\left(x^{2}-2\right)\end{array} \) \( \left(a^{2}+8\right)\left(a^{2}-7\right) \)
Algebra Mexico Feb 26, 2025
Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy